Gender-Based Violence against Men and Women - Warsiti, Warsiti; Rosida, Luluk; Putri, Intan Mutiara; Fajarini, Nurbita (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Based on data from the Indonesian National Commission on Violence Against Women (INCVAW/Komnas Perempuan) from 2007 to 2019, there was a very significant increase in cases of Gender-Based Violence (GBV), reaching eightfold (792%). The majority of GBV victims are women, but men can also be potential victims. However, most research on GBV focuses only on women. Gender-based violence has short-term and long-term impacts on physical and mental health. Female victims of GBV usually experience anxiety, depression, post-traumatic stress disorder (PTSD), and even suicidal thoughts. This study aims to provide an overview of GBV that occurs in both men and women. This study is based on data on reported cases of violence obtained from the Women’s Empowerment and Child Protection Service (WECPS/DP3A) of Sleman Regency, Yogyakarta, for the period 2020-2024. Of the 1,001 reported GBV cases, 817 (81.6%) victims were women and 184 (18.4%) were men. The majority of female victims of GBV are of reproductive age (19-44 years), while the majority of male victims are adolescents (11-18 years). There is a significant relationship between gender, location of the incident, and the type of violence experienced. Currently, both men and women experience violence in the public sphere (50.5% and 53.2%, respectively). Psychological violence is the most common experience for both sexes. Men mostly experience neglect, exploitation, and other forms of violence. Meanwhile, women mostly experience physical, sexual, and human trafficking violence. Innovation in reporting forms that are easily accessible to the public is also needed to facilitate victims seeking help.